DUAL‐energy computed tomography findings in a case of COVID‐19. Issue 1 (23rd June 2021) - Okano, Hiromu; Furuya, Ryosuke; Mishima, Sena; Shimada, Kosuke; Umeda, Sayo; Michishita, Takahiro; Minami, Sakura; Suzuki, Naoya; Hayakawa, Sho; Otsuka, Tsuyoshi; Miyazaki, Hiroshi
Abstract : Background: COVID‐19 pneumonia has lesions with a decreased blood flow. Dual‐energy computed tomography is suitable to elucidate the pathogenesis of COVID‐19 pneumonia because it highlights the blood flow changes in organs. We report the dual‐energy computed tomography findings of a successfully treated case of COVID‐19 pneumonia. Case Presentation: An obese 49‐year‐old man with COVID‐19 pneumonia was transferred from another hospital on day 11 after onset of illness. Although he was hypoxemic (PaO2 /FiO2 = 100), tracheal intubation was not performed after anticipating difficulty in weaning from mechanical ventilation. Prone position therapy and nasal high flow therapy were administered, and the patient was discharged after his condition improved. Dual‐energy computed tomography was performed three times during hospitalization, and it revealed improvement in the blood flow defect, unlike plain computed tomography that did not show much improvement. Conclusion: Dual‐energy computed tomography can assess perfusion in COVID‐19 pneumonia in real time and may be able to predict its severity. Abstract : Dual‐energy computed tomography (DECT) is suitable to elucidate the pathogenesis of COVID‐19 pneumonia because it highlights the blood flow changes in organs. DECT can assess perfusion in COVID‐19 pneumonia in real time and may be able to predict its severity.